Meningkatkan Sumber Daya Manusia dalam Penangkalan Berita Hoaks di Media Sosial Melalui Literasi Digital - Pusporini Palupi Jamaludin; Elizabeth Tika Kristina H; Paringsih Paringsih; Laura Komala (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The aim of the Community Service Activities is to implement one of the Tri Darmas of Higher Education which is carried out by Pamulang University lecturers and students with the title